Pensions - Hill, Michael J. (Michael James), 1937- (Policy and politics in the twenty-first century., 2007)
This book provides a much-needed introductory guide to the issues surrounding pension policy and offers a critique of some of the dominant ideas and assumptions. Noting the intense debate that currently surrounds the subject, the book explores a wider view of the continuing issues about pension policy.